Between the shadow and the geometry of light: Hestnes Ferreira in continuity with Louis Kahn - Saraiva, A. (2017)
This paper intends to show the relevance of light in the work of Louis Kahn and in the work of Hestnes Ferreira in formal and perceptive terms. Raúl Hestnes Ferreira (Lisbon, 1931) is a Portuguese architect who had the privilege of studying and working with Louis I. Kahn between 1963 and 1965. Light, although an external and contingent element of architecture, is a decisive element in terms of definition and perception. Therefore, four works by each architect are compared and analyzed. The results help to highlight the importance of light and shadow in the determination of architectural spaces and how silence enhances the perception of Hestnes Ferreira and Louis Kahn spaces.